PREVENTION OF INCONTINENCE-ASSOCIATED DERMATITIS OF IMMOBILITY PATIENTS USING ALOE VERRA SKIN BARRIER AND OLIVE OIL - Tajarudin, Muhammad; Riyadi, Selamet; Negara, Candra Kusuma (Jurnal EduHealth, 2022)
Incontinence Associated Dermatitis (IAD) is an inflammation of the skin that occurs when urine or faeces come into contact with the perineum, causing discomfort such as pain, burning, and itching in the patient. One IAD management uses skin barriers containing moisturizers such as aloe vera and olive oil. Some of the aloe vera and olive oil compositions benefit the body. Namely, it can accelerate wound healing, anti-inflammatory, moisturize the skin, and antimicrobials. This study aimed to identify the influence of the aloe vera skin barrier and olive oil on iad prevention in immobility patients in hospitals. The population is patients who experience physical immobility and patients who have just entered without IAD at the Haji Adam Malik Central General Hospital Medan. The sample was 11 people (11 people as a control group and 11 as an intervention group), using purposive sampling techniques—data analysis using the Mann Whitney and Kruskal Wallis tests. The results showed differences in IAD values between the three groups, namely the aloe vera, olive oil, and control groups (p= 0.003). The average value of the control is the highest. This means that immunomobility patients who do not get the skin barrier of aloe vera or olive oil experience IAD the most while undergoing treatment at the hospital